2005
DOI: 10.2174/1568026054679290
|View full text |Cite
|
Sign up to set email alerts
|

Donors of HNO

Abstract: Recent comparisons of the pharmacological effects of nitric oxide (NO) and nitroxyl (HNO) donors have demonstrated that the responses to these redox-related nitrogen oxides are nearly universally dissimilar. These analyses have suggested the existence of mutually exclusive signaling pathways as a result of discrete chemical interactions of HNO and NO with a variety of critical biomolecules. Although the mechanisms of action are currently unresolved, the pharmacological responses to HNO are promising for clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 131 publications
(216 reference statements)
2
93
0
Order By: Relevance
“…1 (84,89) The two most commonly used donors of HNO are Angeli's salt (sodium trioxodinitrate, Na 2 N 2 O 3 ) and derivatives of sulfohydroxamic acid, particularly Piloty's acid (benzenesulfohydroxamic acid, C 6 H 5 SO 2 NHOH). Several clinically used compounds such as cyanamide and hydroxyurea can also be bioactivated to HNO [for reviews on HNO donors, see (70,79,80,110)]. …”
Section: Donors Of Hnomentioning
confidence: 99%
See 1 more Smart Citation
“…1 (84,89) The two most commonly used donors of HNO are Angeli's salt (sodium trioxodinitrate, Na 2 N 2 O 3 ) and derivatives of sulfohydroxamic acid, particularly Piloty's acid (benzenesulfohydroxamic acid, C 6 H 5 SO 2 NHOH). Several clinically used compounds such as cyanamide and hydroxyurea can also be bioactivated to HNO [for reviews on HNO donors, see (70,79,80,110)]. …”
Section: Donors Of Hnomentioning
confidence: 99%
“…Such reactions have often been invoked as the basis for the vasoactive properties of HNO donors. In fact, detection of NO in the presence of oxidants, particularly ferricyanide, has long been used as an indirect indicator of HNO production (110). Two-electron oxidants such as flavin adenine dinucleotide (FAD) can also oxidize HNO to NO (52).…”
Section: Hno Reactivitymentioning
confidence: 99%
“…28 For the experimental conditions employed herein (25 °C, pH 7.4, 10 −4 DTPA, aerobic), k 1 was calculated at 8.1 × 10 −4 s −1 . After determination of k on via Angeli's salt calibration, the observed rates of Mn II (NO)TPPS formation were used to calculate HNO concentrations according to: (8) where [Mn II (NO)TPPS] and [Mn III TPPS] concentrations in the film were monitored spectroscopically at 432 and 467 nm, respectively. Considering xerogel film thicknesses (~29 µm) as the optical path length, the extinction coefficient of Mn III TPPS encapsulated in AEMP/MTMOS was calculated to be 90000 M −1 cm −1 at 467 nm via Beer's law.…”
Section: Kinetic Hno Quantificationmentioning
confidence: 99%
“…Although the direct observation of endogenously produced HNO in mammalian cells has remained elusive, CuBOT1 was also used to investigate the generation of HNO from the S-nitrosothiol GSNO and H 2 S. 17 Human umbilical vein endothelial cells (HUVECs) were incubated with 10 µM CuBOT1 In related work, Ivanović-Burmazović and co-workers showed that sodium nitroprusside (Na 2 [Fe(CN) 5 (NO)]; SNP) reacts in live cells to produce HNO. 18 In this study, the authors employed CuBOT1-loaded HUVECs to show that treatment of these cells with either SNP or H 2 S alone did not elicit a significant fluorescence turn-on.…”
Section: Biological Applications Of Cubot1mentioning
confidence: 99%